2010
DOI: 10.1074/jbc.m110.101790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Residue in Helix 2 of Rice Plasma Membrane Intrinsic Proteins That Influences Water Permeability

Abstract: Molecular selection, ion exclusion, and water permeation are well known regulatory mechanisms in aquaporin. Water permeability was found to be diverse in different subgroups of plasma membrane intrinsic proteins (PIPs), even though the residues surrounding the water holes remained the same across the subgroups. Upon homology modeling and structural comparison, a conserved Ala/Ile(Val) residue difference was identified in helix 2 that affected the conformation of the NPA region and consequently influenced the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…All HvPIP1s possessed Ile while the HvPIP2s had Val ( S2 Fig ), suggesting the HvPIP1s may have lower water permeability. Further, the difference between OsPIP1s (lower water permeability) and OsPIP2s (higher water permeability) was attributed to a residue in TM2, where OsPIP1s have Ala and OsPIP2s have Ile/Val [ 25 ]. At this position, HvPIP1;1 and HvPIP1;5 had Ala, but all HvPIP2s as well as HvPIP1;2, HvPIP1;3, HvPIP1;4 had Val ( S2 Fig ), suggesting the latter group may be permeable to water and supporting the observation of Besse et al .…”
Section: Resultsmentioning
confidence: 99%
“…All HvPIP1s possessed Ile while the HvPIP2s had Val ( S2 Fig ), suggesting the HvPIP1s may have lower water permeability. Further, the difference between OsPIP1s (lower water permeability) and OsPIP2s (higher water permeability) was attributed to a residue in TM2, where OsPIP1s have Ala and OsPIP2s have Ile/Val [ 25 ]. At this position, HvPIP1;1 and HvPIP1;5 had Ala, but all HvPIP2s as well as HvPIP1;2, HvPIP1;3, HvPIP1;4 had Val ( S2 Fig ), suggesting the latter group may be permeable to water and supporting the observation of Besse et al .…”
Section: Resultsmentioning
confidence: 99%
“…Point mutations, such as those are able to turn an inactive PIP1 into an active channel without any co-expression, have only been reported for rice PIP1;1 and PIP1;3 (Zhang et al, 2010). In that work, the authors identified by comparative modeling and mutagenesis of one residue (Ala102) in TM2 of Os PIP1;3 located at the interface between monomers that induced, upon mutation into Val, a change in the orientation of Ile101, widening constriction region within the pore.…”
Section: Pip1;2q91l and Pip1;2f220a Are Active Water Channelsmentioning
confidence: 99%
“…PIP1s had an Ala residue, whereas PIP2s had a Val or Ile. In Oryza sativa , this residue was found to be involved in the osmotic water permeability of AQPs [48]. The presence of a Val or Ile residue in helix 2 conferred a high permeability to water of PIP2 members, compared to PIP1 members exhibiting a Ala residue at this location.…”
Section: Resultsmentioning
confidence: 99%